Characteristics of community readiness in the slum area on the edge of the Sulang Saling channel, Medan Denai District regarding relocation plans to flats in Medan City - Budiani, Ina Triesna; Rambe, Yunita Syafitri; Moerni, Saufa Yardha; Barky, Neneng Yulia (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2024)
The 2023 Medan Municipal RPKPP lists the Medan Denai District in the Medan Municipality of North Sumatra as a priority area for addressing slum areas. Slum settlements are being moved to the city's the margins, specifically to apartments in compliance with the City Government's 1000 Towers program, as one of the strategies employed by the government. Relocating to apartments has been implemented poorly, though, with numerous failures. The government's ignorance of the characteristics of the individuals who would be moving to live in apartments and their lack of understanding led to this failure. This research was conducted by conducting a social survey of the people on the outskirts of the Sulang Saling Channel located in Medan Denak District, Medan Municipality, North Sumatra by conducting interviews, observations and distributing questionnaires. Following data sorting and processing based on the research findings, data analysis will be conducted. The Sulang Saling Channel community's traits and preparedness were used to evaluate this study. Three community assessment variables demographics, economic status, and physical attributes are derived from the characteristics. In the meantime, the community's loyalty, involvement, and trust in an organization serve as the assessment variables for community readiness, which includes willingness and readiness. It is evident from the examination of the community's features that the residents of Channel Sulang Saling are suitable to move into apartments. Despite their readiness, only 26.56% were ready to move into flats. This was triggered by their lack of trust in the Government. Meanwhile, their attitudes towards their environmental organizations, their involvement and loyalty towards the organization are quite good, which will later become important when they relocate to an apartment. The results of this research can be used as a reference for relocating people on the outskirts of the Sulang Saling Channel for relocation to flats.